Target interception by mobile robots in a wireless sensor network (I) - Lin, Zhenxing. (2009)
Wireless Sensor Network (WSN) is found to be useful in many technological fields due to its wireless distributed computation capability. A successful attempt in building an experimental test bed for distributed target tracking has led to further improvements to the WSN, the reaction on the tracked target with the objectives to pursuit and intercept the target.